Análisis de la Planta Turística, oferta alojamiento en el Cantón Latacunga - Llundo Telenchana, Maricela Belén (2019)
The situational diagnosis in the Latacunga, has allowed to know the current reality. First, the bibliographic search of the 15 parishes of Latacunga was carried out; as well as the revision of the Plan de Desarrollo y Ordenamiento Territorial (PDOT) 2016 -2028; thus, the information on the tourist accommodation offer was obtained. Information was collected in the municipality of Latacunga and in the different parish councils. A card was created for the recognition of existing establishments within the canton; Subsequently, the information was recorded in the files to obtain reliable data in such a way that the researcher can analyze the tourist accommodation offer and verify if the establishments are in an active state within the canton. A qualitative research was applied, which implies field and bibliographical techniques, thus reliability was obtained in data. The lodging is dispersed by the Latacunga cantón, the inns are located in the rural areas, for the magnitude of space that they need, most of hospitality people do leisure activities; the hotels and hostels are located in the urban parishes, which offer different types of services; the residential are located in the urban area they offer basic services and the shelters are located in national parks and protected areas. Throughout the investigation process it was possible to deduce that Latacunga cantón the owns several lodging establishments, they offer different services according to their categories. The purpose of the research project was to carry out an analysis of the tourist offer in Latacunga cantón, where all data collected was systematized in the design of the catalog, which consists of 9 inns, 26 hotels, 16 hostels, 4 residential and 2 shelters are active, providing service to the visitor.